Fetal hydrometrocolpos with pre-axial mirror polydactyly as a new variant of McKusick-Kaufman syndrome - Kuntharee Traisrisilp (2020)
© 2020 Wiley Periodicals, Inc. This report describes a variant of McKusick-Kaufman syndrome presenting with a large fetal abdominal cyst of hydrometrocolpos at 37 weeks of gestation. The diagnosis was based on the ultrasound findings of a large homogeneous hypoechoic cyst (diameter of >10 cm) with incomplete septum, thickened wall, superiorly connecting to the dilated uterus, consistent with hydrometrocolpos. Additionally, pre-axial mirror polydactyly of the left foot was suspected. Postnatal examination/work-up confirmed the prenatal findings. This is the first report of prenatal diagnosis of hydrometrocolpos with complex polydactyly of mirror image pre-axial duplications containing nine toes instead of six-toe postaxial polydactyly.